PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN DAN STRESS KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA TENAGA MEDIS RSU KALIWATES KABUPATEN JEMBER - Bayu Chandra Cahyono; Raden Andi Sularso; Sumani Sumani (STIE Mandala Jember, 2016)
Organizational culture is a philosophy, ideology, values, assumptions, beliefs, expectations, attitudes and norms that are shared and binding in a particular community. Specifically, the culture in the organization will be determined by conditions of team work, leaders and characteristic of organization and administration process applicable. In addition to the formation of organizational culture, good leadership will also create good kewargaorganisasian behavior. This study aims to identify and examine the influence of organizational culture, leadership and work stress on Organizational citizenship behavior and job satisfaction as an intervening variable in medical personnel RSU Kaliwates Jember. This type of research can be classified as confirmatory research. The population in this research all medical personnel who are in RSU Kaliwates in Jember Jember. Total population of medical personnel who work in public hospitals in Jember Jember Kaliwates there are 59 employees. The sample in this study were selected using census method, where the population being sampled, as many as 59. The analysis tool used is path analysis. Results of this study states that all hypotheses are acceptable and show significant results